Austin Armstrong: capstone - Armstrong, Austin, artist (Colorado State University. Libraries, 2016)
The artist's statement: My work uses visual forms to explore the interplay my personal origins, various religions perspectives, and the way in which we interact with our world. I investigate these concepts by reflecting upon my own origins, both thorough ancestral and spiritual lenses. My imagery is largely drawn from of my personal history, instances of family illness, and archetypes of religious iconography. These tools give way to a wide array of interpretation, while also letting the viewer a glimpse into the concrete and personal space that I create from. A person's beliefs are shaped by the world view that they inherit, as well as the intentions they take in addressing all given situations. This work is a visual symptom, produced by my intentional pursuit of truth amongst my personal beliefs and practices.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: printmaking